Spiritual intelligence and the content of faith: a post-foundational, interdisciplinary and hermeneutical dialogue between Danah Zohar and Dallas Willard - Kilian, Andries P. (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.